2020
DOI: 10.1016/j.stemcr.2019.11.011
|View full text |Cite
|
Sign up to set email alerts
|

iPSC-Derived Platelets Depleted of HLA Class I Are Inert to Anti-HLA Class I and Natural Killer Cell Immunity

Abstract: The ex vivo production of platelets depleted of human leukocyte antigen class I (HLA-I) could serve as a universal measure to overcome platelet transfusion refractoriness caused by HLA-I incompatibility. Here, we developed human induced pluripotent cell-derived HLA-Ideficient platelets (HLA-KO iPLATs) in a clinically applicable imMKCL system by genetic manipulation and assessed their immunogenic properties including natural killer (NK) cells, which reject HLA-I downregulated cells. HLA-KO iPLATs were deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 54 publications
2
59
0
Order By: Relevance
“…Other proposals include overexpressing HLA-E [ 152 ] or retaining the expression of HLA-C [ 153 ]. Interestingly, we found that B2M-KO iPSC-PLTs, which are completely devoid of HLA-I expression, do not elicit an NK cell response in vitro [ 147 ]. To confirm the circulation in vivo in the presence of NK cells, we developed humanized immune system (HIS) mice, which were reconstituted with a sufficient number of human NK cells to reject B2M-knockout iPSC-derived hematopoietic cells.…”
Section: Applying Ipsc-plts To Alloimmune Platelet Transfusion Refracmentioning
confidence: 99%
See 1 more Smart Citation
“…Other proposals include overexpressing HLA-E [ 152 ] or retaining the expression of HLA-C [ 153 ]. Interestingly, we found that B2M-KO iPSC-PLTs, which are completely devoid of HLA-I expression, do not elicit an NK cell response in vitro [ 147 ]. To confirm the circulation in vivo in the presence of NK cells, we developed humanized immune system (HIS) mice, which were reconstituted with a sufficient number of human NK cells to reject B2M-knockout iPSC-derived hematopoietic cells.…”
Section: Applying Ipsc-plts To Alloimmune Platelet Transfusion Refracmentioning
confidence: 99%
“…To confirm the circulation in vivo in the presence of NK cells, we developed humanized immune system (HIS) mice, which were reconstituted with a sufficient number of human NK cells to reject B2M-knockout iPSC-derived hematopoietic cells. B2M-KO iPSC-PLTs circulated comparably with wild-type iPSC-PLTs in the NK cell reconstituted HIS mice and also circulated in the presence of anti-HLA-I antibody [ 147 ]. While this observation removes the concern of NK cells rejecting HLA-KO platelets, the reason for the low immunogenicity of platelets remains unknown.…”
Section: Applying Ipsc-plts To Alloimmune Platelet Transfusion Refracmentioning
confidence: 99%
“…It is estimated that the 10 most frequent lines of iPSCs with homozygous HLA could cover approximately 50% of the Japanese population. Ultimately, owing to the capability of gene editing iPS cells, HLA‐I nullified iPS cell‐derived platelets have also been developed (Feng et al., 2014; Gras et al., 2013; Suzuki et al., 2020) These cells can serve as a universal product and do not require a library of different HLA haplotypes. Furthermore, they are suitable as a platform for further modified products, which may lead to novel therapies using platelets.…”
Section: Ips Cell‐derived Platelets For Hla Compatibilitymentioning
confidence: 99%
“…After differentiation into endothelial-like and cardiomyocyte-like cells, immunogenicity tests revealed no cytokines or antibody response when transplanted into allogenic humanized mice [ 25 ]. Similar approaches have been achieved for the generation of iPSC-derived HLA-universal platelets lacking HLA class I expression by knocking-out β2-Microglobulin gene [ 26 , 27 ]. Taken together, iPSCs can be considered an attractive tool for developing regenerative medicine applications.…”
Section: Ipscs Applicationsmentioning
confidence: 99%